Russian snap military exercise in March of 2015: what implications did this exercise have? - Stiberg, Espen (Fort leavenworth, KS : US Army Command and General Staff College, 2017)
This study examines the Norwegian national military exercise Joint Viking 2015 and a Russian snap exercise that took place in the midst of it. This study examines possible explanations for why Russia responded with this snap exercise, and the possible implications for the Russian response. The study explores the growing importance of the High North and the Arctic region especially regarding Russian strategic military development and as a future base for economic wealth. It underlines the developments in the relationships between Russia, Norway, Sweden, Finland, and NATO during the last decade and after the Ukrainian crisis in 2014. This relationship is arguably at its coldest since the end of the Cold War. The study examines Russia´s military reform and modernization process since 2010 and the use of military exercises to test and validate the results of it. The study concludes that Russia conducted this snap exercise to test its military apparatus and to demonstrate to NATO and the US in particular that their reform and modernization processes have produced results. Further, it demonstrates to any observer that Russia can mobilize rapidly the nation for war, shift substantial forces in its interior to meet any threat, and that Russia is willing to use military force against any threat to the nation.